Discrete typing units of Trypanosoma cruzi identified in rural dogs and cats in the humid Argentinean Chaco - Enriquez, Gustavo Fabián (2013)
The discrete typing units (DTUs) of Trypanosoma cruzi that infect domestic dogs and cats have rarely been studied. With this purpose we conducted a cross-sectional xenodiagnostic survey of dog and cat populations residing in 2 infested rural villages in Pampa del Indio, in the humid Argentine Chaco. Parasites were isolated by culture from 44 dogs and 12 cats with a positive xenodiagnosis. DTUs were identified from parasite culture samples using a strategy based on multiple polymerase-chain reactions. TcVI was identified in 37 of 44 dogs and in 10 of 12 cats, whereas TcV was identified in 5 dogs and in 2 cats -a new finding for cats. No mixed infections were detected. The occurrence of 2 dogs infected with TcIII -classically found in armadillos- suggests a probable link with the local sylvatic transmission cycle involving Dasypus novemcinctus armadillos and a potential risk of human infection with TcIII. Our study reinforces the importance of dogs and cats as domestic reservoir hosts and sources of various DTUs infecting humans, and suggests a link between dogs and the sylvatic transmission cycle of TcIII.